Cover Feature: Electrospun Nanofibers for Wound Management (ChemNanoMat 7/2022). Issue 7 (20th June 2022) - John, Johnson V.; McCarthy, Alec; Karan, Anik; Xie, Jingwei
Abstract : Electrospun nanofibers have been widely examined for various biomedical applications. This review reports recent advances in electrospun nanofibers for wound management. We first describe how to use nanofiber materials and incorporate clotting factors can stop bleeding. Then, we show how to use nanofiber materials for delivery of antimicrobial agents and analgesics, to combat infection and relieve the pain. We further discuss how to combine the delivery of therapeutics (e.g., growth factors, cells, skin tissues) with nanofiber materials for enhancing wound healing. Finally, we present the conclusions and future perspectives in terms of the use of electrospun nanofibers for wound management. More information can be found in the Minireview by Jingwei Xie et al.